The efficacy of transcutaneous vagus nerve stimulation in heart failure management - a systematic review and meta-analysis - Zongmei Sun; Lin Liu; Haijun Peng; RunFeng Zhang (BMC Cardiovascular Disorders)
Abstract Background Heart failure (HF) is a prevalent global health concern characterized by elevated mortality and morbidity rates. Non-invasive transcutaneous vagus nerve stimulation (t-VNS) has emerged as a potential therapeutic intervention for improving cardiac function and alleviating clinical symptoms in HF patients by modulating autonomic nervous system equilibrium. Methods We conducted a comprehensive and systematic search across various scholarly databases, including PubMed, the Cochrane Library, CNKI, and Web of Science, to identify RCTs examining the therapeutic benefits of t-VNS in patients with HF. Statistical analysis of the results was carried out using the random-effects model in Review Manager 5.3 software. The research protocol has been registered in the PROSPERO registry with the registration number CRD42024570589. Results The analysis included ten RCTs involving a collective sample of 374 patients with HF. The meta-analysis results revealed that t-VNS treatment significantly increased LVEF (MD 3.21, 95% CI 1.46 to 4.95, P = 0.0003), improved GLS (MD -2.31, 95% CI -3.52 to -1.10, P = 0.0002), enhanced 6-MWD (MD 86.6 m, 95% CI 59.55 to 113.65, P < 0.00001), reduced MLHFQ score (MD -13.32, 95% CI -19.38 to -7.26, P < 0.00001), lowered TNF-α levels (MD -1.47, 95% CI -2.36 to -0.59, P = 0.001), and Significantly reduced HR (MD -4.24, 95% CI -8.27 to -0.22, P = 0.04), t-VNS exhibited good tolerability with no reported adverse events. Conclusion t-VNS represents a promising therapeutic modality for heart failure, providing advantages such as improved cardiac function, enhanced well-being, reduced inflammatory marker levels, reduced HR and favorable safety profile.